2016
DOI: 10.1111/zph.12263
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pasteurella multocida Infections – Report of Five Cases at a Minnesota Hospital, 2014

Abstract: Summary During October 2014, the Minnesota Department of Health was notified of five Hospital A patients with Pasteurella multocida bacteraemia; three had died. Human soft tissue infection with P. multocida typically results from cat or dog bites or scratches. Invasive infection, defined as a P. multocida isolate from a usually sterile site, is rare. We evaluated P. multocida isolations at Hospital A, compared with other Minnesota hospitals to understand invasive infection trends. A case was defined as clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Dog bites are a major public health problem worldwide [ 1 , 2 , 3 ]. As a result of these incidents, important consequences emerge, among which are physical injuries, psychological trauma, zoonotic disease transmission [ 4 , 5 , 6 ], infections [ 7 , 8 , 9 ], dysfunction of injured body parts and economic costs [ 10 ], both for the state of the country in question, as well as for the victims of these episodes. Internationally, in underdeveloped and developing countries, highly lethal zoonotic diseases such as rabies occur, which is mainly transmitted by free-roaming dog bites [ 9 ], estimating that 99% of infections are produced by this type of incident [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dog bites are a major public health problem worldwide [ 1 , 2 , 3 ]. As a result of these incidents, important consequences emerge, among which are physical injuries, psychological trauma, zoonotic disease transmission [ 4 , 5 , 6 ], infections [ 7 , 8 , 9 ], dysfunction of injured body parts and economic costs [ 10 ], both for the state of the country in question, as well as for the victims of these episodes. Internationally, in underdeveloped and developing countries, highly lethal zoonotic diseases such as rabies occur, which is mainly transmitted by free-roaming dog bites [ 9 ], estimating that 99% of infections are produced by this type of incident [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…P. multocida has a zoonotic potential and infection to human spread through bites and scratches of the animals (especially dogs and cats) (Aski & Tabatabaei, 2016). The infection may lead to ocular infection to fatality in humans (Corchia et al, 2015;Talley et al, 2016). Shivachandra et al (2013) studied the genetic relatedness of ptfA gene among P. mutocida isolates of different species and observed that avian isolates are divergent from mammalian isolates .…”
Section: Haemorrhagic Septicaemia (Hs)mentioning
confidence: 99%
“…P. multocida is a gram negative encapsulated non-motile coccobacillus. It forms part of the normal flora in the oropharynx and nasopharynx but can also be a pathogen [21] . Animal exposure; usually from the scratch, bite or lick of a domestic cat or dog, is an important risk factor and is present in most cases of Pasteurella infection [21] , [22] .…”
Section: Discussionmentioning
confidence: 99%